THE QUALITY OF TEACHER-MADE MULTIPLE-CHOICE TEST USED AS SUMMATIVE ASSESSMENT FOR ENGLISH SUBJECT - Santy, Ni Putu Liana; Dewi, Ni Luh Putu Eka Sulistia; Paramartha, Anak Agung Gede Yudha (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2020)
This study analyzed the quality of multiple-choice test used as middle test made by the English teachers in one school in Singaraja. This study was essential to be conducted since the items of the multiple-choice test must have good quality to be used to assess the students’ achievement levels. This study used content analysis method in analyzing100 items from 3 different instruments. In collecting the data, the checklist analysis form was used to compare the items of teacher-made multiple-choice test with the norms as one of the standards in making a good multiple-choice test, then clarified through interview. From the data that have been obtained, there are 72% of students who got bad scores in the middle test. There is 1% of the items has sufficient quality, 8% of items have good quality, and the rest of the items have very good quality. The most common mistake found is in the punctuation and capitalization. It is supported by the results of the interview, which show that the teachers did not know precisely the norm of punctuation and capitalization. It can be concluded that the teachers already follow the norms of making a multiple-choice test, and it is indicated that the quality of the multiple-choice test is not the only factor that affects students’ achievement levels.Keywords: instrument quality, norms, teacher-made multiple-choice test